Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Pratique du pouvoir et idée de Nature (1) L'appropriation des femmes - Guillaumin, Colette (Questions Féministes, 1978)
Dans les relations entre classes de genre, le fait que les hommes puissent s'assurer la force de travail des femmes sans contrepartie mesurable (en temps, en argent, etc.) montre que la nature de la relation est différente de celle de la vente de travail classique. Comme dans l'esclavage et le servage, il y a appropriation directe de la base matérielle – corporelle – de l'individu. Cette appropriation se manifeste, dans la forme matrimoniale de cette relation, par le fait que le travail n'est pas évalué, par l'appropriation des produits – parmi lesquels les enfants –, par le droit illimité d'utiliser le corps de la femme. Elle s'exprime par la nature de certaines tâches : la responsabilité, par exemple, des besoins corporels du dominant et des siens. Ces tâches sont empiriquement associées à l'appropriation corporelle (du parti dominé), dans l'esclavage par ex.
Keywords: 1900-1999; approches et analyses; corps; cours; discipline; division sexuelle du travail; europe; fem1000; france; incontournable; lit3220; pol4212; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques